ANALISIS METODE ARIMA PADA PERAMALAN NILAI EKSPOR SUMATERA BARAT - irwandi irwandi; Devni Prima Sari (Journal of Mathematics UNP, 2021)
The movement of the export value of the province of West Sumatra every month experiences a fluctuating condition and tends to decline. Exports are very important for the economy in a region. The decline in the value of exports allows a decrease in the amount of production of goods which can result in weakening economic growth in the region. The non-constant export value needs to be analyzed so that it can be used as an indicator for the West Sumatra government in taking policies that maximize export value, such as increasing competence and skills to produce products that are able to compete in the export market. So it is necessary to forecast the export value of the province of West Sumatra so that the government can take some planning in the future. This study aims to determine the form of the forecasting model and the results of forecasting the export value of West Sumatra for the period January 2021 to December 2021. The forecasting method used is the ARIMA method. The results show that the ARIMA (2,1,0) model is a suitable model for predicting the export value of West Sumatra, with the model Y_t=0,00131+0,5265Y_(t-1)+0,1705Y_(t-2)+0,3030Y_(t-3)+e_t.